Lipoprotein binding and endosomal itinerary of the low density lipoprotein receptor-related protein in rat liver. - Lund, H (1989)
The high affinity of 45Ca binding to the low density lipoprotein receptor (LDL-R) and the LDL-R-related protein (LRP) was utilized to study the subcellular distribution of these two proteins in rat liver. Like the LDL-R, LRP was manyfold enriched in rat liver endosomal membranes with a relative distribution in early and late endosomal compartments consistent with recycling between endosomes and the cell surface. The high concentration of LRP in hepatic endosomal membranes greatly facilitated demonstration of Ca-dependent binding of apolipoprotein E- and B-containing lipoproteins in ligand blots. LRP was severalfold more abundant than the LDL-R in hepatic parenchymal cells, showed extensive degradation in hepatic endosomes, and was found in high concentrations in the Golgi apparatus and endoplasmic reticulum. These data suggest a high rate of synthesis of LRP that appeared to be unaffected by treatment of rats with estradiol. The repeating cysteine-rich A-motif found in the ligand-binding domain of LRP appeared to be responsible for Ca binding by LRP, LDL-R, and complement factor C9 and accounted for immunological cross-reactivity among these proteins. Weaker ligand-blotting properties and an extraordinary susceptibility to proteolysis most likely contribute to the difficulty of detecting LRP in conventional assays for lipoprotein receptors. Our data suggest an extensive proteolytic processing of this protein and are consistent with a functional role of LRP in lipoprotein metabolism.